1983
DOI: 10.1016/0014-5793(83)81134-x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of optically pure (−)‐[3H]nicotine to rat brain membranes

Abstract: With the recent availability of ( -)-[3H]nicotine of high specific activity, binding studies were performed on rat brain membranes in the presence of a variety of nicotine analogues and cholinergic drugs. Both a higher affinity (& = 2 x lo-" M) and a lower affinity (2 x 10e9 M) site were observed; the stereoselectivity of both sites being similar. A good correlation was observed between Z&-values and psychotropic potency of a series of N'alkyl substituted nicotine analogues. Nicotine receptor Rat brain Nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 8 publications
0
12
1
1
Order By: Relevance
“…A stereoselective difference in the physiological effects of nicotine is wellknown (Hicks et al, 1947;Barlow and Hamilton, 1965). The (+) (R)-nicotine is according to physiological studies and receptor binding data less potent than the (-) (S)-nicotine in rodents (Aceto et al, 1979;Martin and Aceto, 1981;Abood et al, 1983). Both enantiomers bind to two classes of nicotinic binding sites although there are 10-fold differences in affinity for the high affinity site.…”
Section: Discussionmentioning
confidence: 97%
“…A stereoselective difference in the physiological effects of nicotine is wellknown (Hicks et al, 1947;Barlow and Hamilton, 1965). The (+) (R)-nicotine is according to physiological studies and receptor binding data less potent than the (-) (S)-nicotine in rodents (Aceto et al, 1979;Martin and Aceto, 1981;Abood et al, 1983). Both enantiomers bind to two classes of nicotinic binding sites although there are 10-fold differences in affinity for the high affinity site.…”
Section: Discussionmentioning
confidence: 97%
“…Stereospecific binding of nicotine enantiomers has been demonstrated for high and low affinity binding sites in the central nervous system, and in the periphery for binding sites at the nicotinic receptor of the autonomic and the somatic nervous systems (Meltzer et al 1980;Romano and Goldstein 1980;Martin and Aceto 1981;Ikushima et al 1982;Abood et al 1985;Sloan et al 1985;Aceto et al 1986;Henley and Oswald 1987;Goldberg et al 1989). The quantitative differences in binding values (IC 50 ) of nicotine enantiomers seem to be small compared to the differences observed for the stereoisomers of opioids.…”
Section: Introductionmentioning
confidence: 94%
“…The quantitative differences in binding values (IC 50 ) of nicotine enantiomers seem to be small compared to the differences observed for the stereoisomers of opioids. Abood et al (1985) found a threefold greater IC 50 value for R(+)-nicotine than for S(9)-nicotine at the higher affinity site and twice that at the lower affinity site. The affinity of opioids to the mu1-receptor was 10-fold higher for R(+)-than for S(9)-methadone (Kristensen et al 1995).…”
Section: Introductionmentioning
confidence: 94%
“…Also, both chronic nicotine and mec exposure increase cell surface NGF receptors in PC-12 cells [Terry and Clarke, 1994], and nicotine exhibits a high affinity for [ 3 H]-mec binding sites [Banerjee et al, 1990]. Mec does not compete at the so-called nicotinic recognition site [Marks and Collins, 1982;Abood et al, 1983;Varanda et al, 1985], however. The observation that nicotine demonstrates affinity at [ [Rozental et al, 1989].…”
Section: Response Latenciesmentioning
confidence: 99%